The effects of diet and supplements on a male world champion lightweight rower - Xia, G.; Chin, M. K.; Girandola, R. N.; Liu, R. Y. (The Journal of Sports Medicine and Physical Fitness, 2001)
A world-class lightweight rower who came to the Hong Kong Sports Institute was evaluated over a two-month period of training. He was preparing for the 1995 World Rowing Championships. The subjects trained for approximately 70 minutes per day at different levels of intensity, to simulate race conditions. Caloric expenditures (based upon heart rate response and estimation from specific activity) were estimated to be approximately 4125 kcal/day. A three day dietary survey revealed that the subject was able to maintain caloric balance (caloric intake = 4088 kcal/day). Body weight was maintained at a constant level, another indication that the subject was able to meet energy needs. A breakdown of his food intake revealed protein, carbohydrate, and fat, made up 19%, 51%, and 30% of his caloric intake, respectively. This was somewhat surprising since recommendations for endurance athletes are for higher carbohydrate contribution. During and after the training bouts the subject consumed two separate carbohydrate supplements. A total of 218 g of carbohydrate were consumed daily. This level of supplementation was able to maintain the subject's blood glucose concentration at normal levels following recovery from exercise. Comparisons of recovery heart rates when either water or carbohydrate was consumed indicate a beneficial effect of the supplement. Despite consuming carbohydrates at lower than recommended levels, this athlete went on to win this third gold medal in rowing.